Rheological Properties Of Titanium Alloy (Ti6Al4V) - Wollastonite (W) Composite Using Palm Stearin as Based Binder / Mohd Ikram Ramli...[et al.] - Ramli, Mohd Ikram; Sulong, Abu Bakar; Muhamad, Norhamidi; Muchtar, Andanastuti; Zakaria, Mohd Yusuf (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Powder injection molding (PIM) is a net-shaping process that can fabricate complex shaped of products in large quantities by using metal and ceramic powders. Biocompatible materials such as titanium alloy (Ti6Al4V) and wollastonite (W) have been widely used as bone implant's applications. However, no reports on a fabrication of Ti6Al4V-W composite using PIM process have been reported. In this study, the Ti6Al4V/W powders with the weight percentage (wt.%) ratio of 90:10, 80:20 and 70:30, were mixed with a binder system of palm stearin and polyethylene to obtain the feedstocks. It was found that for the feedstock of 90:10, the flow behavior at 130°C and 150°C is dilatant compared to 170°C where the flow is pseudoplastic. For the feedstocks of 80:20 and 70:30, the flow behavior was pseudoplastic. The rheological properties of such a feedstocks were analyzed using Shimadzu CFT-500D capillary rheometer. The lowest activation energy of 0.227 kJ/mol was obtained. All feedstocks were found to be in the range of injectability index for PIM process. There was a powder-binder separation phenomenon occurred on the green part of 90:10 wt.%while at 70:30 (wt.%), a good surface contact between the powder and binder was observed.